O amadurecimento da personagem em Mrs. Dalloway, de Virginia Woolf - Assis, Emanuelle Perissotto [UNESP] (2011)
The corpus of this study is the novel Mrs. Dalloway, by Virginia Woolf, published in 1925. According to the writer Harold Bloom, while writing Mrs. Dalloway, Woolf thought of an order structure such that each scene would establish the idea of the character of Clarissa. The heroine's subjective universe is constructed scene by scene through the hours that run in London one day apparently common. The day that begins at ten am and ends at 3 am the other, involves not only personal and important findings deepen the understanding of his own human condition. The objective of this paper is to show how, in Mrs. Dalloway, the progression of hours in the space of one day, get through the poetic narrative and the use of psychological and chronological time, clearing the mind of the characters - focusing on single Clarissa Dalloway's character - culminating in his personal growth and social, is to understand the reason for their existence or, after all, considered a key and important in the world, finding motivations for why they live